DYNAMICS OF ECHOCARDIOGRAPHIC PARAMETERS IN HEALTHY GIRLS BORN WITH CONGENITAL HEART DEFECTS FROM BIRTH TO ONE YEAR - Saidova Sadokat Yo`ldoshovna (Zeta Repository, 2023)
In the presented scientific work, the causes and complications of congenital heart defects in children were explained from the literature. This article provides information on the incidence of congenital heart defects among children and the risk of sympatry.